Directions For Sustainable Development of Forestry with Low Greenhouse Gas Emissions - Svetlana S. MORKOVINA; Anna V. IVANOVA (Communications of International Proceedings, 2024)
In the context of increasing anthropogenic pressure, climate-smart forestry is one of the approaches to achieving the goals of its sustainable development. The basic component of sustainable development of forestry is movement in accordance with the trajectory of scientific and technological development of the industry. The work analyzed the scientific research of scientists, as a result of which the directions of advanced research carried out for the sustainable development of forestry with low greenhouse gas emissions were established. Next, in the identified areas, a predictive expert-analytical assessment of the prospects for technologies for sustainable development of forestry in the Russian Federation with low greenhouse gas emissions was carried out. It has been proven that the highest priority technologies include technologies for assessing the vulnerability of forest ecosystems to climate change and technologies for increasing the productivity of the depositing capacity of forest ecosystems. The overall result of the bibliometric study confirms the high scientific interest in conducting research on the identified priority technologies.
Keywords: sustainable development; forestry; greenhouse gases; priority technologies